Tourism: A Fuzzy Concept? - Dewailly, Jean-Michel (Turyzm/Tourism, 2002)
The author has observed that books and publications about tourism usually need to begin by defining the concept, and that each definition given is slightly different from the next. From this observation, the author assumes that although tourism is a fuzzy concept a definition is nevertheless necessary. The WTO definition actually seems the ‘least appropriate’, but can - even must - be adapted according to research circumstances. Recognizing the fuzzy nature of tourism seems firstly to correspond to a general trend in academic research, secondly to satisfy the need for professionals and scholars to have only a single common definition, thirdly to allow the inclusion of new practices and products which mix business and pleasure, and fourthly to allow consideration of the human dimension of tourism, which in turn implies a more humanistic approach.